Synthesis and characterization of a carboxyl‐terminated waterborne hyperbranched polymer and its coordination behavior with chromium(III). Issue 8 (16th November 2013) - Li, Chenying; Chen, Hualin; Liu, Bailing; Wang, Bin; Luo, Rong; Shan, Ning
ABSTRACT Despite its irreplaceable position in the leather industry, chrome tanning has been listed in the procession of limitation. The serious environmental pollution caused by chrome tanning through the residual chrome it leaves in wastewater has attracted great attention. To improve the absorption of chrome and reduce chromium emission, a novel hyperbranched ligand was synthesized and characterized. The impact elements of the coordination process between the hyperbranched oligomer and Cr(III) was investigated, and the characteristics of the complex are also discussed. This hyperbranched oligomer had a low molecular weight (weight‐average molecular weight = 2125) and narrow molecular weight distribution (PDI = 1.21). The time required for the coordination process between the hyperbranched oligomer and Cr(III) was around 6 h, and the optimum pH was 4.0. Moreover, the complex exhibited alkali resistance and fair resistance to oxidation; this suggested that this developed hyperbranched ligand is a potential masking agent or tanning auxiliary for chrome tanning and will enable improvements in chromium absorption. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40117.